2019
DOI: 10.1111/1540-6229.12274
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Impact of Monetary Policy on Regional Housing Prices in the United States

Abstract: This article uses a factor-augmented vector autoregressive model to examine the impact of monetary policy shocks on housing prices. To simultaneously estimate the model parameters and unobserved factors, we rely on Bayesian estimation and inference. Policy shocks are identified using high-frequency surprises around policy announcements as an external instrument. Impulse response functions reveal differences in regional housing price responses, which in some cases are substantial. The heterogeneity in policy re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 45 publications
4
19
0
Order By: Relevance
“…Consistent with our findings for Australia, there is substantial variation across US local housing markets in the sensitivity of housing prices to monetary policy (Fratantoni and Schuh 2003; Cooper, Luengo‐Prado and Olivei 2016; Fischer et al 2018; Xie 2019). This heterogeneity is typically linked to variation in housing supply elasticities (Glaeser et al 2008; Xie 2019) and, more specifically, to variation in local government regulations (Fischer et al 2018). There is also some evidence of asymmetric effects of monetary policy across US local housing markets (Aastveit and Anundsen 2016).…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Consistent with our findings for Australia, there is substantial variation across US local housing markets in the sensitivity of housing prices to monetary policy (Fratantoni and Schuh 2003; Cooper, Luengo‐Prado and Olivei 2016; Fischer et al 2018; Xie 2019). This heterogeneity is typically linked to variation in housing supply elasticities (Glaeser et al 2008; Xie 2019) and, more specifically, to variation in local government regulations (Fischer et al 2018). There is also some evidence of asymmetric effects of monetary policy across US local housing markets (Aastveit and Anundsen 2016).…”
Section: Introductionsupporting
confidence: 84%
“…However, some studies suggest that monetary policy has a limited role to play in explaining the variation across local housing markets (Del Negro and Ortok 2007). Moreover, while many studies suggest that regional heterogeneity is due to supply‐side factors, other potential explanations could be important too (for example, Fischer et al 2018; Beraja et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A reasonable explanation for this is that most of the characteristics affect both the level of housing prices and the loan-to-value ratio. In an interesting and recently published article, Fisher et al (2019), the effect of monetary policy on regional housing markets around the US is also analyzed. The results from their VAR model and impulse response functions using monthly data from 1997 to 2012 show that the effect can vary considerably between regions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Overall, the empirical results of this study have verified that interest rate variation affects home price behavior, and home prices tend to fall into disequilibrium or correct themselves anytime in the housing market when the economic environment involves a substantial decrease in interest rates. Previous studies have reported that interest rates affect housing prices (Fischer et al, 2019;Hanck & Prüser, 2020;Valadkhani et al, 2019) and result in housing bubbles (Jordà et al, 2015;Moons & Hellinckx, 2019). Other studies have identified that money supply affects housing prices (Su et al, 2019;Yin et al, 2020) and bubbles (Tsai, 2015b;Huang & Shen, 2017).…”
Section: Home Price Behaviormentioning
confidence: 98%